Humidifying laminate and humidifier

By using porous reinforcing materials and non-porous membranes with charged parts in the moisture-permeable laminate of the humidifier, the problem of burying scale components and flying bacteria is solved, and long-term high-efficiency moisture permeability and anti-fouling effects are achieved.

CN119343231APending Publication Date: 2025-01-21DAICEL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380045926.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-15
Filing Date
2023-06-12
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the existing moisture permeable membrane humidifier, the scale component is prone to landfill the holes of the laminated body, resulting in a decrease in the function of the moisture permeable layer, and the problem of scattering of miscellaneous bacteria or scale components is difficult to effectively suppress.

Method used

A porous reinforced material is laminated with a non-porous membrane. The non-porous membrane is composed of a thermoplastic resin with a cationic part or an anionic part. It inhibits the adhesion and scattering of scale components through repulsion and optimizes permeability through the separation structure of the hydrophilic part and the hydrophobic part. Moisture.

Benefits of technology

It achieves high long-term moisture permeability of the humidification laminate, effectively suppresses the scattering of scale components and bacteria, and extends the service life of the humidifier.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343231A_ABST
    Figure CN119343231A_ABST
Patent Text Reader

Abstract

Provided is a humidification laminate that can exhibit sufficient moisture permeability over a long period of time and that can suppress the scattering of impurities such as infectious microbes and scale components. A humidification laminate (1) is provided with a porous reinforcing material (11) and a non-porous film (12) which is laminated on at least one surface of the porous reinforcing material (11) and functions as a moisture-permeable film, and the non-porous film (12) contains a thermoplastic resin having a cationic part or an anionic part. Furthermore, the non-porous membrane (12) is disposed on the water side of the liquid with respect to the porous reinforcing material (11), preferably for absorbing the water of the liquid and releasing the water into the air, and the cationic portion preferably contains a group containing ammonium ions or a group capable of forming ammonium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a humidifying laminate and a humidifier. In addition, this application claims priority to Japanese Patent Application No. 2022-096877 filed in Japan on June 15, 2022, the contents of which are incorporated herein by reference. Background Art

[0002] In connection with the recent spread of infectious diseases, it is now required to maintain relative humidity above a certain level not only for ventilation but also to eliminate viruses. As a device that achieves both ventilation and humidification, for example, a moisture permeable membrane humidifier is known.

[0003] As a moisture permeable layer of a conventional moisture permeable membrane humidifier, a moisture permeable layer using a laminate (sheet) of a porous substrate and a hydrophilic nonwoven fabric and having holes for water vapor permeation in the laminate is known.

[0004] However, it is known that such a moisture-permeable layer has a problem that scale components generated in the humidifier fill the pores of the laminate, and the function of the moisture-permeable layer is degraded due to long-term use.

[0005] As a method of suppressing the adhesion and accumulation of such scale components, for example, Patent Document 1 discloses a technique in which a material containing hydrophilic cations is coated on a filter portion so that the cation portion repels the scale components and the adhesion and accumulation of the scale components are suppressed.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-2126 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, since Patent Document 1 is an invention of a rotary humidifier using a filter, a water layer needs to be formed on the filter for humidification, and there is a problem that bacteria and scale components are scattered from the water layer together with water vapor.

[0011] In order to suppress the scattering of such bacteria and scale components, a moisture permeable membrane type humidifier using a moisture permeable membrane is effective.

[0012] Therefore, an object of the present disclosure is to provide a humidifying laminate that can exhibit sufficient moisture permeability for a long period of time and can suppress the scattering of impurities such as bacteria and scale components.

[0013] Solutions for solving problems

[0014] The inventors of the present disclosure have conducted in-depth research to achieve the above-mentioned purpose, and found that the following humidification laminate can exert sufficient moisture permeability for a long time and can inhibit the scattering of impurities such as bacteria and scale components, and the humidification laminate has: a porous reinforcing material; and a non-porous film, which is laminated on at least one surface of the porous reinforcing material and functions as a moisture permeable film, wherein the non-porous film contains a thermoplastic resin having a cationic part or an anionic part. The present disclosure relates to a substance completed based on these insights.

[0015] That is, the present disclosure provides a humidifying laminate, which is a laminate comprising: a porous reinforcing material; and a nonporous film laminated on at least one surface of the porous reinforcing material and functioning as a moisture-permeable film, wherein the nonporous film contains a thermoplastic resin having a cationic portion or an anionic portion.

[0016] The humidifying laminate of the present disclosure has excellent moisture permeability and can suppress the scattering of bacteria, scale components, etc. by having a non-porous film that functions as a moisture permeable film. In addition, by having a cationic part or anionic part in the thermoplastic resin, a repulsive force is generated between the cationic part or the anionic part and the scale components, which can suppress the scale components from adhering / accumulating on the moisture permeable layer, and can continuously exert moisture permeability for a long time.

[0017] The non-porous membrane is preferably disposed on the water side of the liquid relative to the porous reinforcing material, and is used to absorb water from the liquid and release it into the air.

[0018] The cationic portion preferably contains a group containing an ammonium ion or a group capable of forming an ammonium ion. By containing a group containing an ammonium ion or a group capable of forming an ammonium ion, the nonporous membrane can exert a bactericidal effect, thereby further inhibiting the adhesion / accumulation of miscellaneous bacteria and the like.

[0019] Preferably, the thermoplastic resin has a hydrophilic portion, and the hydrophilic portion contains a structural unit represented by the following formula (1). The nonporous membrane can form a water conduction path in the nonporous membrane due to the hydrophilic portion having the structural unit, and can easily exhibit moisture permeability.

[0020] [Chemical formula 1]

[0021]

[0022] (R1 and R2 independently represent a hydrogen atom or a methyl group.)

[0023] In addition, it is preferred that the thermoplastic resin has a hydrophobic portion, and the hydrophobic portion contains a structural unit represented by the following formula (2) and / or the following formula (3). The nonporous membrane can form a water-conducting path in the nonporous membrane by having the hydrophobic portion of the structural unit, and can easily exhibit moisture permeability.

[0024] [Chemical formula 2]

[0025]

[0026] (R1 represents a hydrogen atom or a methyl group, and R3 represents a hydrogen atom or an alkyl group having 1 to 2 carbon atoms.)

[0027] [Chemical formula 3]

[0028]

[0029] (R1 represents a hydrogen atom or a methyl group, and R4 represents a branched alkyl group having 3 or more carbon atoms.)

[0030] In addition, the nonporous film preferably contains an antiseptic. By containing an antiseptic, the growth of various bacteria can be suppressed, and the scattering of various bacteria can be easily suppressed.

[0031] In addition, the average particle size of the antiseptic is preferably larger than the film thickness of the nonporous film. By making the average particle size of the antiseptic larger than the film thickness of the nonporous film, the antiseptic can function as an anti-blocking agent.

[0032] Furthermore, the above-mentioned nonporous film preferably contains an anti-blocking agent.

[0033] In addition, the average particle size of the anti-blocking agent is preferably larger than the thickness of the non-porous film. By having the above structure, when the non-porous films are in contact with each other, adhesion can be prevented, and moisture permeability can be easily exerted for a longer period of time.

[0034] Furthermore, the nonporous film preferably contains a leveling agent.

[0035] In the humidifying laminate, it is preferred that the nonporous film is applied so as to cover at least one surface of the porous reinforcing material.

[0036] Furthermore, the present invention provides a humidifier provided with a plurality of bag-shaped water-retaining containers formed by bonding the above-mentioned humidifying laminate to a frame.

[0037] Furthermore, the present disclosure provides an air conditioner equipped with the above-mentioned humidifier.

[0038] Furthermore, the present disclosure provides a ventilation device equipped with the above-mentioned humidifier.

[0039] In addition, the present disclosure provides an air purifier equipped with the above-mentioned humidifier.

[0040] Beneficial Effects

[0041] The humidification laminate of the present disclosure can exhibit sufficient moisture permeability for a long period of time, and can suppress the scattering of impurities such as bacteria and scale components. Therefore, the humidification laminate of the present disclosure is preferably used in a moisture permeable membrane type humidifier. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic cross-sectional view showing one embodiment of the humidification laminate of the present disclosure. DETAILED DESCRIPTION

[0043] The humidifying laminate of one embodiment of the present disclosure at least has: a porous reinforcing material; and a non-porous membrane, which is provided on at least one surface of the porous reinforcing material. The non-porous membrane can be provided on a single side of the reinforcing material, or on both sides. In addition, the humidifying laminate can also be a structure in which the non-porous membrane is clamped by two of the porous reinforcing materials. That is, the porous reinforcing material can also be provided on both sides of the non-porous membrane. In this case, the two porous reinforcing materials can be the same porous reinforcing materials, or they can be porous reinforcing materials with different materials, thicknesses, etc.

[0044] Figure 1 1 is a schematic cross-sectional view showing one embodiment of the humidifying laminate of the present disclosure. The humidifying laminate 1 includes a porous reinforcing material 11 and a non-porous membrane 12 provided on one surface 11 a of the porous reinforcing material 11 .

[0045] <Non-porous membrane>

[0046] The non-porous membrane contains a thermoplastic resin, and the thermoplastic resin has a cationic part or an anionic part. Therefore, the non-porous membrane has the cationic part or the anionic part. When metal ions are used as the main raw material, in the area where cationic scale components are easily generated, and when a large amount of water containing the above-mentioned cationic scale components is used, the non-porous membrane preferably has a cationic part. When silicon dioxide or the like is used as the main raw material, in the area where anionic scale components are easily generated, and when a large amount of water containing the above-mentioned anionic scale components is used, the non-porous membrane preferably has an anionic part. By having the above-mentioned structure, the non-porous membrane can exert a repulsive force on the scale components and can inhibit the attachment / accumulation of the scale components to the non-porous membrane.

[0047] In addition, the non-porous film is a moisture permeable film. In order to make the non-porous film absorb moisture, the thermoplastic resin preferably has a hydrophilic part. In addition, in order to form a water-conducting passage in the non-porous film, the thermoplastic resin preferably has a hydrophobic part. Therefore, the thermoplastic resin preferably has both a hydrophilic part and a hydrophobic part. It is speculated that: in the non-porous film, by forming a structure in which the hydrophilic part is separated from the hydrophobic part, the hydrophilic part functions as a water-conducting passage, which allows more water vapor to pass through, so the moisture permeability is more excellent.

[0048] Examples of the thermoplastic resin include acrylic resins, cellulose resins, polyester resins such as polybutylene terephthalate, polyether resins, polyurethane resins, polyvinyl chloride resins, polyethylene, polystyrene resins, polyamide resins, polyacetal resins, polycarbonate resins, polyphenylene sulfide resins, polyetheretherketone, polyimide resins, polytetrafluoroethylene resins, polycaprolactone, and polylactic acid.

[0049] As described above, the thermoplastic resin preferably has a hydrophilic portion, a hydrophobic portion, and a cationic portion or anionic portion, and is therefore preferably a thermoplastic copolymer containing different monomer components.

[0050] The hydrophilic part is preferably composed of a monomer (a) (hereinafter referred to as monomer (a)) unit containing a hydrophilic functional group in a side chain in the structural unit of the copolymer. In addition, the hydrophobic part is preferably composed of a monomer (b) (hereinafter referred to as monomer (b)) unit containing a hydrophobic functional group in a side chain. In addition, the hydrophilic part and the hydrophobic part are preferably formed in the copolymer. In the non-porous film, the copolymer can maintain a core-shell structure in which the hydrophobic part is formed inside and the hydrophilic part is formed outside. In this case, the hydrophilic part and the hydrophobic part can be formed by the core and shell of two or more adjacent copolymers. In addition, the copolymer can also be a core-shell structure before the non-porous film is formed, and the core-shell structure is not maintained when the non-porous film is formed.

[0051] The copolymer preferably contains a structural unit derived from the monomer (a) as a part constituting the hydrophilic part. As the monomer (a), for example, there can be listed: a monomer containing a glycidyl group, a monomer containing a hydrolyzable silyl group, a monomer containing an acetoacetyl group, a hydroxyl group-containing monomer, and a carboxyl group-containing monomer. Among them, preferably a carboxyl group-containing monomer, methyl (meth)acrylate, and a monomer having a cationic functional group and a monomer having an anionic functional group described later. The monomer (a) can be used alone or in combination of two or more. It should be noted that "(meth)acrylic acid" in this specification means at least one of "acrylic acid" and "methacrylic acid".

[0052] As said glycidyl group-containing monomer, glycidyl (meth)acrylate, (meth)allyl glycidyl ether, etc. are mentioned, for example.

[0053] Examples of the hydrolyzable silyl group-containing monomer include vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, and vinyl methyl dimethoxysilane; and (meth) acryloxy silyl group-containing monomers such as γ-(meth)acryloxypropyl trimethoxysilane, γ-(meth)acryloxypropyl methyl dimethoxysilane, γ-(meth)acryloxypropyl triethoxysilane, and γ-(meth)acryloxypropyl methyl diethoxysilane.

[0054] Examples of the acetoacetyl group-containing monomer include allyl diacetoacetate, acetoacetoxyethyl (meth)acrylate, acetoacetoxyethyl crotonate, acetoacetoxypropyl (meth)acrylate, acetoacetoxypropyl crotonate, and 2-cyanoacetoacetoxyethyl (meth)acrylate.

[0055] Examples of the hydroxyl group-containing monomer include hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.

[0056] Examples of the carboxyl group-containing monomer include acid anhydride monomers such as crotonic acid, maleic acid, and maleic anhydride, fumaric acid, citraconic acid, glutaconic acid, itaconic acid, acrylamide N-glycolic acid, cinnamic acid, and (meth)acrylates.

[0057] Furthermore, as the monomer (a), methyl (meth)acrylate and / or (meth)acrylate are particularly preferred, that is, the hydrophilic portion preferably includes a structural unit represented by the following formula (1).

[0058] [Chemical formula 1]

[0059]

[0060] (R1 and R2 each independently represent a hydrogen atom or a methyl group.)

[0061] The content of the monomer (a) is preferably 20 to 70 mol%, more preferably 30 to 70 mol%, and further preferably 40 to 60 mol% relative to the total monomer components constituting the copolymer. By adjusting the content of the monomer (a) within this range, a hydrophilic portion can be formed in the nonporous membrane, and a water-conducting path can be easily formed, resulting in better moisture permeability.

[0062] The copolymer preferably contains a structural unit derived from the monomer (b) as a part constituting the hydrophobic portion. The monomer (b) is not particularly limited, but preferably contains a monomer having a hydrocarbon group with a carbon number of 2 or more, and more preferably, a (meth)acrylate having a hydrocarbon group with a carbon number of 2 or more can be cited. The monomer (b) can be used alone or in combination of two or more.

[0063] Examples of the hydrocarbon group having 2 or more carbon atoms include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a group in which two or more of these are bonded to each other.

[0064] Examples of the aliphatic hydrocarbon group include alkyl, alkenyl, and alkynyl. Examples of the alkyl group include straight or branched alkyl groups such as ethyl, propyl, isopropyl, butyl, isobutyl, hexyl, octyl, isooctyl, decyl, dodecyl, and stearyl. Examples of the alkenyl group include straight or branched alkenyl groups such as vinyl, allyl, methallyl, 1-propenyl, isopropenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, and 5-hexenyl. Examples of the alkynyl group include straight or branched alkynyl groups such as ethynyl and propynyl.

[0065] Examples of the alicyclic hydrocarbon group include cycloalkyl groups having 3 to 12 carbon atoms such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl and cyclododecyl; cycloalkenyl groups having 3 to 12 carbon atoms such as cyclohexenyl; and bridged hydrocarbon groups having 4 to 15 carbon atoms such as bicycloheptyl and bicycloheptenyl.

[0066] Examples of the aromatic hydrocarbon group include aryl groups having 6 to 14 carbon atoms (particularly aryl groups having 6 to 10 carbon atoms), such as phenyl and naphthyl.

[0067] The hydrocarbon group having 2 or more carbon atoms is preferably an aliphatic hydrocarbon group or an aromatic hydrocarbon group, and more preferably a linear or branched alkyl group or an aromatic hydrocarbon group.

[0068] Specifically, the monomer (b) is preferably a monomer capable of forming a structural unit represented by the following formula (2) and / or the following formula (3). That is, the hydrophobic portion preferably includes a structural unit represented by the following formula (2) and / or the following formula (3).

[0069] [Chemical formula 2]

[0070]

[0071] (R1 represents a hydrogen atom or a methyl group, and R3 represents a hydrogen atom or an alkyl group having 1 to 2 carbon atoms.)

[0072] [Chemical formula 3]

[0073]

[0074] (R1 represents a hydrogen atom or a methyl group, and R4 represents a branched alkyl group having 3 or more carbon atoms.)

[0075] In the above formula (2), the bonding position of R3 may be any of the hydrocarbons constituting the benzene ring. Examples of monomers capable of forming the structural unit represented by the above formula (2) include styrene, α-methylstyrene, p-methylstyrene, p-ethylstyrene, and the like.

[0076] In the above formula (3), the carbon number of R4 is preferably 3 to 10. Examples of the monomer capable of forming the structural unit represented by the above formula (3) include isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.

[0077] The content of the monomer (b) is preferably 20 mol% to 70 mol% relative to the total monomer components constituting the copolymer, more preferably 30 mol% to 70 mol%, and further preferably 40 mol% to 60 mol%. By adjusting the content of the monomer (b) within this range, a hydrophobic portion can be formed in the nonporous membrane to easily form a water-conducting path, and the moisture permeability is more excellent.

[0078] In addition, the thermoplastic resin has a cationic part or an anionic part. The thermoplastic resin may have a cationic part or an anionic part in the hydrophilic part and / or the hydrophobic part, or may have a cationic part or an anionic part in other places. In addition, the thermoplastic resin preferably has a cationic part or an anionic part in the hydrophilic part, and the thermoplastic resin preferably has both a cationic part and an anionic part. The cationic part is preferably a cationic functional group or a group that can generate a cationic functional group. The group that can generate a cationic functional group refers to a group that does not have a cationic functional group at the stage of the thermoplastic resin, but generates a cationic functional group at the stage of forming the nonporous membrane and when used. In addition, the cationic functional group may also be a zwitterionic functional group having both cations and anions.

[0079] As the above-mentioned cationic functional group, for example, a nitrogen-containing group can be listed. As the above-mentioned nitrogen-containing group, a group containing ammonium ions or a group capable of forming ammonium ions can be listed. Here, the above-mentioned group capable of forming ammonium ions refers to a group that is not ionized at the stage of the above-mentioned thermoplastic resin, and forms an ionized body at the stage of forming the above-mentioned non-porous membrane and when used. As the above-mentioned group containing ammonium ions and the group capable of generating ammonium ions, for example, cyclic groups containing nitrogen atoms such as primary amino groups, secondary amino groups, tertiary amino groups, quaternary ammonium groups, imino groups (-NH- groups and =NH groups), amidine groups, imino groups, hydrazine groups, amide groups, imide groups, pyridyl groups, etc. can be listed. In addition, as the above-mentioned zwitterionic functional group, for example, a quaternary ammonium-containing group can be listed. As the above-mentioned quaternary ammonium-containing group, for example, a betaine group, a phosphorylcholine group, etc. can be listed. Among the above thermoplastic resins, from the viewpoint of exerting antibacterial properties and preventing bacteria from flying from the nonporous film, groups capable of generating ammonium ions after the nonporous film is formed are preferred, and groups capable of generating quaternary ammonium groups (quaternary ammonium groups, imide groups) are more preferred.

[0080] When the thermoplastic resin is the copolymer, the copolymer preferably contains a structural unit derived from a monomer having a cationic functional group in a side chain. Examples of the monomer having a cationic functional group include monomers having the nitrogen-containing group as a functional group. Examples of the monomer having the nitrogen-containing group as a functional group include amide group-containing monomers, amino group-containing monomers, and imide group-containing monomers. Examples of the amide group-containing monomer include: N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di(n-butyl) (meth)acrylamide, N,N-di(tert-butyl) (meth)acrylamide and the like N,N-dialkyl (meth)acrylamide; N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-n-butyl (meth)acrylamide and the like N-alkyl (meth)acrylamide; N-vinylacetamide, N-(2-hydroxyethyl) (meth)acrylamide, N- N-hydroxyalkyl (meth)acrylamide such as amine, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, and N-(4-hydroxybutyl) (meth)acrylamide; N-alkoxyalkyl (meth)acrylamide such as N-methoxymethyl (meth)acrylamide, N-methoxyethyl (meth)acrylamide, and N-butoxymethyl (meth)acrylamide; and N,N-dimethylaminopropyl (meth)acrylamide and N-(meth)acryloyl morpholine. In addition, examples of amino group-containing monomers include substituted or unsubstituted amino group-containing (meth)acrylates such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate. In addition, examples of monomers containing an imide group include N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyhexamethylene succinimide, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide. The above monomers having a cationic functional group may be used alone or in combination of two or more.

[0081] The content of the monomer having a cationic functional group is preferably 0.5 mol% to 10 mol%, more preferably 1 mol% to 7 mol%, and further preferably 2 mol% to 5 mol% relative to all monomer components constituting the copolymer. By adjusting the content of the monomer having a cationic functional group within this range, repulsion with scale components can be exerted, and adhesion / accumulation of scale components to the non-porous membrane can be suppressed.

[0082] The anionic moiety is preferably an anionic functional group. Examples of the anionic functional group include anionic groups such as a carboxyl group, a sulfone group, and a phosphoric acid group.

[0083] When the thermoplastic resin is the copolymer, the copolymer preferably contains a structural unit derived from a monomer having an anionic functional group in a side chain. Examples of the monomer having an anionic functional group include monomers having the anionic functional group described above. Examples of the monomer having an anionic functional group include carboxyl-containing monomers, sulfonic acid-containing monomers, and phosphoric acid-containing monomers.

[0084] The content of the monomer having anionic functional groups is preferably 0.5 mol% to 10 mol%, more preferably 1 mol% to 7 mol%, and further preferably 2 mol% to 5 mol% relative to all monomer components constituting the copolymer. By adjusting the content of the monomer having anionic functional groups within this range, repulsion with scale components can be exerted, and adhesion / accumulation of scale components to the non-porous membrane can be suppressed.

[0085] In addition, the above-mentioned copolymer may also contain a structural part derived from a crosslinking agent. As the above-mentioned crosslinking agent, as long as it is a compound that can be crosslinked with the side chain of the monomer constituting the above-mentioned copolymer, there is no particular limitation. For example, a difunctional body preferably has two reactive functional groups. From the viewpoints of increasing the width of the density of the crosslinking density in the polymer, adjusting the mechanical properties, etc., a trifunctional or higher crosslinking agent can be used. As the above-mentioned crosslinking agent, for example, difunctional or higher epoxy-containing compounds, difunctional or higher isocyanate-containing compounds, etc. can be listed. In the above-mentioned copolymer, from the aspect of being able to generate quaternary ammonium ions after the crosslinking reaction with the functional group formed in the side chain, it is particularly preferred to contain difunctional or higher epoxy-containing compounds.

[0086] Examples of the epoxy group-containing compound include bisphenol A and epichlorohydrin type epoxy compounds, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl aniline, N,N,N',N'-tetraglycidyl-m-xylene diamine (e.g., trade name "TETRAD-X", manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (e.g., trade name "TETRAD-C", manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0087] The amount of the crosslinking agent used is preferably 1 to 60 mol parts relative to the total amount (100 mol parts) of the reactive side chains of the copolymer, more preferably 2 to 30 mol parts, and further preferably 4 to 15 mol parts. By adjusting the amount of the crosslinking agent used within this range, a water-conducting path can be easily formed in the nonporous membrane, making it easy to make the moisture permeability excellent.

[0088] The weight average molecular weight of the thermoplastic resin is not particularly limited, but is preferably 20,000 to 2,000,000, more preferably 30,000 to 1,500,000, further preferably 50,000 to 1,000,000, and particularly preferably 70,000 to 500,000. The weight average molecular weight is a value calculated based on polystyrene conversion by gel permeation chromatography (GPC).

[0089] (Other ingredients)

[0090] The nonporous film may contain other components besides the thermoplastic resin within a range that does not impair the effects of the humidification laminate of the present disclosure.

[0091] The above-mentioned moisture permeable layer preferably contains an antiseptic as the above-mentioned other component. As the above-mentioned antiseptic, known mildew inhibitors, antibacterial agents, etc. can be used. In addition, from the viewpoint of functioning as an anti-adhesive agent, the average particle size of the above-mentioned antiseptic is preferably larger than the thickness of the above-mentioned moisture permeable layer, and from the viewpoint of not being easy to fall off from the above-mentioned moisture permeable layer, the average particle size of the above-mentioned antiseptic can be smaller than the thickness of the above-mentioned moisture permeable layer. In addition, the above-mentioned antiseptic can be used only one kind, or two or more kinds can be used in combination.

[0092] The content of the preservative is preferably 0.1 to 10 parts by mass relative to the total amount (100 parts by mass) of the copolymer, more preferably 0.15 to 3 parts by mass, and particularly preferably 0.2 to 2 parts by mass. By making the preservative the above content, sufficient antibacterial properties can be exerted, the performance reduction of the non-porous membrane caused by bacteria can be suppressed, and the humidification laminate can be easily made to exert a long-term effect.

[0093] The above-mentioned non-porous film preferably includes an anti-blocking agent. By including the above-mentioned anti-blocking agent, it is easy to reduce the water contact angle in the above-mentioned non-porous film, and when the above-mentioned laminate is stored as a winding body, it is easy to suppress the adhesion of the above-mentioned porous reinforcing material connected to the above-mentioned non-porous film. In addition, when the above-mentioned non-porous films contact each other, it is also easy to suppress adhesion.

[0094] The average particle size of the anti-blocking agent is preferably 0.5 μm to 5 μm, more preferably 1 μm to 4 μm, and particularly preferably 1.5 μm to 3 μm.

[0095] In addition, the average particle size of the anti-blocking agent is preferably larger than the film thickness of the non-porous film, more preferably 0.1 μm to 3 μm larger than the film thickness of the non-porous film, and particularly preferably 0.3 μm to 2 μm larger than the film thickness of the non-porous film. By making the average particle size of the anti-blocking agent larger than the film thickness of the non-porous film, the non-porous film can be made to have concavoconvexity, and the ground contact area when the films contact each other can be reduced, so adhesion can be suppressed. In addition, from the viewpoint of forming a non-porous film, it is preferably less than 3 μm as an upper limit.

[0096] As the above-mentioned anti-adhesion agent, preferably fluorine-based, silicon dioxide-based and chitosan-based anti-adhesion agents. In addition, as the above-mentioned anti-adhesion agent, it is preferably included in combination with the release agent described later. By using the above-mentioned anti-adhesion agent, it is also possible to easily suppress the adhesion of the above-mentioned non-porous film and the above-mentioned porous reinforcing material. As the above-mentioned anti-adhesion agent, silicon dioxide-based and chitosan-based are more preferably used. The above-mentioned anti-adhesion agent can be used only one, or two or more can be used in combination.

[0097] As the above-mentioned fluorine-based anti-adhesive agent, triperfluorooctyl phosphate and triperfluorododecyl phosphate can be listed. As the silica-based anti-adhesive agent, natural silica particles and synthetic silica particles can be listed. As the above-mentioned chitosan-based anti-adhesive agent, for example, chitosan nanofibers can be listed.

[0098] The content of the anti-blocking agent is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and particularly preferably 1 to 3 parts by mass relative to the total amount (100 parts by mass) of the copolymer. By making the anti-blocking agent the above content, it is easy to take into account both sufficient anti-blocking performance and moisture permeability.

[0099] The non-porous film may also include a release agent. As the release agent, a silicone-based release agent may be cited. The release agent exerts a release effect in the non-porous film. In the present disclosure, the release effect refers to the property of being easy to peel off again after bonding. By using a material that exerts the release effect, the non-porous film has water resistance, which can make it easy to peel off again after the non-porous films are in contact with each other.

[0100] Examples of silicone-based release agents include dimethyl polysiloxane, etc. The silicone-based release agents may be modified, and examples of modified silicones include amino-modified silicones, epoxy-modified silicones, and hydrophilic polyether-modified silicones, etc. The release agents may be used alone or in combination of two or more.

[0101] The content of the release agent is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and particularly preferably 1 to 3 parts by mass relative to the total amount (100 parts by mass) of the copolymer. By making the release agent the above content, it is easy to achieve both sufficient waterproofness and moisture permeability.

[0102] Furthermore, the nonporous film may contain a leveling agent. The leveling agent may be used alone or in combination of two or more.

[0103] The content of the leveling agent is preferably 0.1 to 10 parts by mass, more preferably 0.15 to 3 parts by mass, and particularly preferably 0.2 to 2 parts by mass relative to the total amount (100 parts by mass) of the copolymer. When the content of the leveling agent is within the above range, a nonporous film can be easily formed.

[0104] The thickness of the non-porous film is not particularly limited, and is preferably 0.5 μm to 5 μm, and more preferably 1 μm to 4 μm. If the thickness is 0.5 μm or more, the film-forming property becomes good, which is related to the improvement of gas barrier properties. In addition, the non-porous film has a tendency to have excellent moisture permeability when the thickness is thick. It is speculated that the reason is that the water content of the non-porous film is high. In addition, if the thickness is 5 μm or less, it is easy to form a film, and the economy is also excellent.

[0105] The above-mentioned copolymer has a hydrophilic part and a hydrophobic part, causing the above-mentioned non-porous membrane to have a structure in which the hydrophilic part and the hydrophobic part are separated on the surface. The maximum diameter of the hydrophilic part in the above-mentioned non-porous membrane surface is preferably less than 50nm, more preferably less than 20nm. If the maximum diameter of the above-mentioned hydrophilic part is less than 50nm, the material with a size exceeding 50nm is not easy to penetrate the above-mentioned non-porous membrane, and the above-mentioned non-porous membrane can be used as a barrier film (barrier film) that does not allow materials (such as viruses, etc.) above 50nm to penetrate. The diameter of the above-mentioned hydrophilic part is evaluated by the following method. By using the adhesion measurement mode of a scanning probe microscope (SPM), the part with high adsorption force (hydrophilic part) and the part with low adsorption force (hydrophobic part) are digitized by adhesion, and processed using image analysis software, the diameter of the hydrophilic part can be calculated in the form of equivalent circle diameter. In addition, the above-mentioned maximum diameter is the diameter with the largest diameter in the diameter (equivalent circle diameter) of the hydrophilic part calculated as described above.

[0106] It should be noted that in the present disclosure, the structure in which the maximum diameter of the hydrophilic portion is below 50nm does not substantially penetrate components of a size of 50nm or more, and therefore substantially only penetrates water vapor, so the pores of the non-porous membrane in the present disclosure do not include pores below 50nm formed in the hydrophilic portion. In addition, when the maximum diameter of the hydrophilic portion exceeds 50nm, there is a possibility of permeating other components other than water vapor, and therefore a membrane having a structure in which the maximum diameter of a plurality of the hydrophilic portions exceeds 50nm is defined as a porous membrane.

[0107] The non-porous film is preferably a layer formed by coating. Since it is formed by coating, it can be easily made into a non-porous film, and it is easy to suppress the scattering of scale components, bacteria, etc.

[0108] <Porous reinforcement material>

[0109] Preferably, the porous reinforcing material is an element that serves as a support for the nonporous membrane and has excellent moisture permeability.

[0110] As the material forming the above-mentioned porous reinforcing material, any one of hydrophilic material and hydrophobic material can be used, but hydrophobic material is preferably used.If the above-mentioned hydrophobic material is used, when the composition for forming a non-porous film is applied, the composition does not penetrate into the porous reinforcing material, so in the porous reinforcing material, there is no need to prevent the guiding substrate from flowing down from the face opposite to the film forming face.

[0111] As the material forming the above-mentioned porous reinforcing material, for example, can be listed: organic matter such as polyolefin resin, cellulose resin, polycarbonate resin, polyamide resin, polyimide resin, polyamide-imide resin and fluorine resin, inorganic matter such as metal, glass and ceramic etc.Wherein, because the above-mentioned non-porous film can be made into film with lower temperature on the above-mentioned porous reinforcing material, in addition, from the viewpoint of excellent moisture permeability and water resistance, it is preferably organic matter, as the above-mentioned organic matter, it is particularly preferably polyolefin resin.The above-mentioned material can also be fibrous such as metal fiber, inorganic fiber.The material forming the above-mentioned porous reinforcing material can be only one kind, can also be two or more.

[0112] Examples of the porous reinforcing material include a resin porous film, an inorganic porous film, a metal porous film, and a fibrous substrate.

[0113] The polyolefin resin is a polymer (including an olefin elastomer) composed of an olefin as an essential monomer component, that is, a polymer containing at least a structural unit derived from an olefin in a molecule (in one molecule). The olefin is not particularly limited, and examples thereof include α-olefins such as ethylene, propylene, 1-butene, and 4-methyl-1-pentene.

[0114] Examples of the polyolefin resin include polymers containing ethylene as an essential monomer component (polyethylene resins), polymers containing propylene as an essential monomer component (polypropylene resins), ionomers, and amorphous cyclic olefin polymers.

[0115] The porosity of the porous reinforcing material is not particularly limited, but is preferably 30% to 90% by volume, more preferably 40% to 70% by volume. If the porosity is 30% by volume or more, the moisture permeability becomes better. If the porosity is 90% by volume or less, the supporting performance of the nonporous membrane becomes better.

[0116] The thickness of the porous reinforcing material is not particularly limited, but from the viewpoint of fully supporting the nonporous film, it is preferably more than 5 μm, more preferably more than 10 μm. In addition, considering excellent moisture permeability and economy, the thickness of the porous reinforcing material is preferably less than 50 μm, more preferably less than 30 μm.

[0117] From the viewpoint of being able to easily form the nonporous film, the surface of the porous reinforcing material on the side having the nonporous film (for example, Figure 1 The surface 11a shown in (11) is preferably hydrophilized. Particularly, when a hydrophobic material is used as the material forming the above-mentioned porous reinforcing material, the above-mentioned hydrophilization is preferably implemented. As the above-mentioned hydrophilization, corona discharge treatment, plasma treatment, etc. can be listed. Through these hydrophilization, carboxyl, hydroxyl or carbonyl can be generated on the porous reinforcing material surface, and the composition used to form the above-mentioned non-porous film is easily wetted and expanded on the porous reinforcing material surface, and the above-mentioned non-porous film is easily formed. In addition, thus, the adhesion of the above-mentioned porous reinforcing material and the above-mentioned non-porous film is improved. In addition, when the above-mentioned porous reinforcing material formed by the hydrophobic substrate is kept as a winding body, the form in which one face of the above-mentioned porous reinforcing material contacts with the other face in the winding body, but because a hydrophilic face contacts with the hydrophobic other face, adhesion can be prevented.

[0118] The surface tension of the surface of the porous reinforcing material on one side of the non-porous film is preferably 35dyn / cm to 55dyn / cm, and more preferably 37dyn / cm to 50dyn / cm. If the surface tension is 35dyn / cm or more, it is easy to apply the composition for forming the non-porous film, and it is easy to form the non-porous film. If the surface tension is 55dyn / cm or less, the composition for forming the non-porous film can not be excessively wetted and expanded, and the non-porous film can be easily formed on the surface of the porous reinforcing material. It should be noted that when the surface of the porous reinforcing material is hydrophilized, the surface on one side of the non-porous film is the surface to which the hydrophilization treatment is applied.

[0119] The surface tension of the inside of the above-mentioned porous reinforcing material (that is, the inside of the region where the above-mentioned non-porous film is not formed) is preferably less than 35dyn / cm, more preferably less than 33dyn / cm. If the above-mentioned surface tension is less than 35dyn / cm, the composition for forming the above-mentioned non-porous film can be suppressed from penetrating into the inside of the above-mentioned porous reinforcing material, and the above-mentioned non-porous film is easily formed on the surface of the above-mentioned porous reinforcing material. It should be noted that, when the surface of the above-mentioned porous reinforcing material has been hydrophilized, the inside of the above-mentioned porous reinforcing material is the inside of the region where the hydrophilization treatment is not implemented. In addition, the surface tension of the above-mentioned inside can be obtained by measuring the cross section obtained by cutting off the above-mentioned porous reinforcing material.

[0120] [Laminate for humidification]

[0121] The above-mentioned humidifying laminate is tested for moisture permeability according to JIS Z0208-1976 (cup method). A moisture permeable cup with 40 g of water is placed in a constant temperature and humidity chamber under the conditions of a temperature of 20°C, a relative humidity of 65%, and a wind speed of 0.1 m / s. The reduction in the total mass of the water and the moisture permeable cup after 1 hour is converted into the moisture permeability of the test piece per 1 m 2 The moisture permeability of the mass for 24 hours is preferably more than 1350 g / (m 2 ·24h), more preferably 1370g / (m 2 The above-mentioned humidifying laminate has excellent moisture permeability, so the above-mentioned moisture permeability can be more than 1350g / (m 2 ·24h) structure.

[0122] In addition, the above-mentioned humidifying laminate is subjected to the moisture permeability test method (cup method) of JIS Z0208-1976. A moisture permeable cup with 40 g of water is placed in a constant temperature and humidity chamber under the conditions of a temperature of 20°C, a relative humidity of 30%, and a wind speed of 2.4 m / s. The reduction in the total mass of the water and the moisture permeable cup after 1 hour is converted into the moisture permeability of the test piece per 1 m 2 The moisture permeability of the mass for 24 hours is preferably more than 18000 g / (m 2 ·24h), more preferably 19000g / (m 2 ·24h) or more, more preferably 20000g / (m 2 The above-mentioned humidifying laminate has excellent moisture permeability, so the above-mentioned moisture permeability can be more than 18000g / (m 2 ·24h) structure.

[0123] The humidifying laminate is preferably prepared by heating the rolled sheet at 70°C for 15 hours, and then pulling out the sheet by hand to suppress adhesion between the moisture permeable layer and the porous reinforcing material. The humidifying laminate can be easily manufactured and stored as a rolled body by suppressing adhesion between the moisture permeable layer and the porous reinforcing material.

[0124] In the two humidifying laminates made of the above-mentioned humidifying laminates in the shape of 25mm×100mm strips, water is dripped onto the non-porous membrane side of one humidifying laminate, and then the non-porous membrane side of the other humidifying laminate is laminated so that water is spread over the entire surface. The laminated humidifying laminate is heated at 55°C for 1 hour, and the peel strength when the peel strength is measured by Tensilon is preferably 4N / 25mm or less, more preferably 2N / 25mm or less, and further preferably 0.5N / 25mm or less. By making the above-mentioned peel strength 4N / 25mm or less, even if the above-mentioned moisture permeable layers are in contact with each other, it is easy to peel off again, and it is easy to suppress adhesion.

[0125] [Method for producing a humidifying laminate]

[0126] The disclosed humidification laminate can be made by forming the above-mentioned non-porous film using a known or customary method on at least one surface of the above-mentioned porous reinforcing material.For example, the above-mentioned non-porous film can be directly formed on a surface of the above-mentioned porous reinforcing material, or after the above-mentioned non-porous film is temporarily formed on other supports, transfer (lamination) is applied to a surface of the above-mentioned porous reinforcing material, thus forming the above-mentioned non-porous film on the porous reinforcing material.Wherein, from the viewpoint of the excellent adhesion of the above-mentioned non-porous film and the above-mentioned porous reinforcing material, the method of the former is preferably used.

[0127] The surface of the porous reinforcing material on the side where the nonporous membrane is provided may be subjected to a hydrophilic treatment. Examples of the hydrophilic treatment include the above-mentioned treatments.

[0128] The nonporous film can be formed by coating (applying) the composition for forming the nonporous film onto the porous reinforcing material or the other support, and removing the solvent from the obtained coating film by heating or the like.

[0129] Since the porous reinforcing material is subjected to the hydrophilization treatment to suppress blocking, it can be produced by a roll-to-roll method in which a non-porous film is formed on the porous reinforcing material previously made into a rolled body and then the rolled body is made again.

[0130] The above-mentioned composition can be made by a known or customary method. For example, the above-mentioned copolymer can be made by dissolving or dispersing it in a solvent, and mixing additives such as preservatives as needed. As the above-mentioned solvent, water and / or a water-soluble solvent are preferred. It can be inferred that when water or a water-soluble solvent is used, the above-mentioned copolymer is dispersed in the composition in a core-shell shape with the inner side being the hydrophobic portion and the outer side being the hydrophilic portion. By using such a composition, the hydrophilic portion is separated from the hydrophobic portion when the coating is dried, and a non-porous film is formed in a state with a water-conducting channel. In addition, it can be inferred that the hydrophobic portion becomes a state of being firmly bonded to each other, and water resistance becomes better.

[0131] Examples of the water-soluble solvent include aliphatic water-soluble alcohols such as methanol, ethanol, n-propanol, and isopropanol; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monoethyl ether; and the like. The water-soluble solvent may be used alone or in combination of two or more.

[0132] The ratio (concentration) of the above-mentioned copolymer in the above-mentioned composition in which the above-mentioned copolymer is dissolved or dispersed is not particularly limited, and is preferably 0.5 to 5% by mass, more preferably 1 to 4% by mass, and further preferably 1.5 to 3% by mass. If the above-mentioned concentration is less than 5% by mass, the thickness of the coating layer thickens, so the film thickness of the non-porous film after drying is further uniformized. Thus, a non-porous film with excellent gas barrier properties and further thin filmization can be formed, and as a result, moisture permeability is further improved. In addition, if the above-mentioned concentration is within the above-mentioned range, the coating property is excellent, and in addition, a non-porous film with excellent moisture permeability and gas barrier properties is easily formed.

[0133] It should be noted that the coating (applying) of the above-mentioned composition can also utilize known coating methods. For example, coating machines such as gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, bar coater, knife coater, spray coater, comma coater, direct coater, etc. can also be used. Formed by such coating, thus easily form a non-porous film.

[0134] The heating temperature when the above-mentioned coating film is desolvated is preferably 35°C to 90°C, more preferably 40°C to 85°C, and further preferably 45°C to 80°C. The heating time can be appropriately used for an appropriate time, for example, 5 seconds to 20 minutes, preferably 5 seconds to 10 minutes, and more preferably 10 seconds to 5 minutes. The above-mentioned composition can be used to form a non-porous film at a low temperature below 90°C (especially below 80°C), so it is easy to form a film. In addition, a polyolefin resin with excellent moisture permeability can be used as a porous reinforcing material.

[0135] The humidifying laminated body in which the non-porous film is formed on at least one surface of the porous reinforcing material by the above method has low air permeability and excellent moisture permeability. It should be noted that the humidifying laminated body refers to a laminated body that enables water vapor to move through the humidifying laminated body. Therefore, the humidifying laminated body can be preferably used for products requiring such functions, for example, a moisture permeable membrane humidifier, a total heat exchange device, a lining of clothing, a disposable waterproof / moisture permeable material; a purpose of dehydration without exposure to air and bacteria (a filter for storing cooked meat, etc.), etc. In addition, the humidifying laminated body has a structure in which the hydrophilic part and the hydrophobic part are separated, so it can also be used as a barrier film with moisture permeability. In the case where the diameter of the hydrophilic part is small, since it is a barrier film with the above moisture permeability, a small-sized substance (such as water vapor) with hydrophilicity is allowed to pass through the hydrophilic part, and a large-sized substance (such as a virus) is not allowed to pass through the hydrophilic part, thereby separating the two.

[0136] [Bag-shaped water-retaining container]

[0137] By covering the outside of the frame with the humidification laminate, a bag-shaped water-retaining container can be produced.

[0138] The frame is preferably made of a rigid material, such as resin, metal / alloy material, etc. In addition, the frame may be a plate-shaped or bag-shaped frame produced by extrusion molding, a plate-shaped frame produced by injection molding, or a bag-shaped structure produced by laminating two or more plate-shaped frames. In addition, the hole portion may be provided after the bag-shaped frame is produced, or a frame with the hole portion provided in advance may be produced.

[0139] Preferably, a part or the whole of the contact portion between the laminate and the frame is bonded. The method of bonding to the frame is not particularly limited, and the laminate can be bonded by bonding using a known or commonly used adhesive, or by welding using ultrasonic welding, high-frequency welding, thermal welding, or the like.

[0140] The above method can be used to make a bag-shaped water-retaining container. The bag-shaped water-retaining container has a stacked body arranged outside a frame structure, and the water of the liquid introduced into the bag-shaped water-retaining container is absorbed by the stacked body as water vapor, diffuses in the stacked body, and can release water vapor from the entire stacked body.

[0141] In addition, a humidifier can be manufactured by mounting a plurality of the bag-shaped water-retaining containers. Such a humidifier has improved humidification performance compared to the past, so it can achieve the same performance while miniaturizing the humidifier, and is also excellent in terms of cost.

[0142] The humidifier includes the humidifying laminate, and can maintain performance for a long period of time while suppressing the scattering of bacteria, scale components, and the like, and can therefore be suitably used in air conditioners, ventilators, air purifiers, and the like.

[0143] Each scheme disclosed in this specification may also be combined with any other feature disclosed in this specification. Each configuration and combination of configurations in each embodiment is an example, and appropriate addition, omission, substitution and other changes of configurations may be made within the scope of the present disclosure. In addition, each invention disclosed in this disclosure is not limited by the embodiments and the following examples, but only by the patent claims.

[0144] Example

[0145] Hereinafter, one embodiment of the present disclosure will be described in more detail based on examples.

[0146] Example 1

[0147] 100 parts by mass of thermoplastic resin solution A was diluted with 22 parts by mass of ethanol and 143 parts by mass of distilled water to prepare a coating solution with a resin concentration of 10% by mass. The thermoplastic resin solution A contained: 47 parts by mass of isobutyl acrylate and 1 part by mass of styrene as structural units forming the hydrophobic part of the polymer; 21 parts by mass of acrylic acid and 28 parts by mass of methyl acrylate as structural units forming the hydrophilic part; 3 parts by mass of imide as structural units forming the cationic part; and 2 parts by mass of epoxy compound as a crosslinking agent. On the other hand, one surface of a porous substrate made of polypropylene resin (thickness: 20 μm, porosity: 48% by volume) was corona treated to form a hydrophilic surface with a surface tension of 39 dyn. Then, the above composition was applied to the hydrophilic surface of the above porous reinforcing material using a wire rod, and heated at 70°C for 1 minute to form a non-porous film (thickness: 1 μm). In this way, a humidifying laminate of Example 1 was produced.

[0148] Embodiments 2 to 5

[0149] A humidifying laminate was produced in the same manner as in Example 1 except that the components marked with circle were added as shown in Table 2 to prepare a coating liquid.

[0150] The details of each component in Table 2 other than the above are described below.

[0151] Silica fine particles A: trade name "SYLYSIA 300", manufactured by FUJI SYLYSIA CHEMICAL CO., LTD., average particle size 1.7 μm.

[0152] Silica fine particles B: trade name "MP-4540M", manufactured by Nissan Chemical Co., Ltd., average particle size 0.45 μm.

[0153] Silicone: trade name "X-51-1264", manufactured by Shin-Etsu Chemical Co., Ltd.

[0154] Chitosan: trade name "EFo-08002", manufactured by SUGINO MACHINE CO., LTD.

[0155] [evaluate]

[0156] Each humidifying laminate obtained in the embodiment and the comparative example was evaluated as described below. The evaluation results are recorded in the table. It should be noted that "-" in the table means that no evaluation was performed or that the evaluation could not be performed. The porous substrate made of polypropylene resin without forming a non-porous film was evaluated as comparative example 1.

[0157] (1) Moisture permeability

[0158] For the humidifying laminates obtained in the examples and comparative examples, the moisture permeability was measured based on the moisture permeability test method (cup method) of JIS Z0208-1976. Specifically, the humidifying laminates obtained in the examples and comparative examples were left to stand in the measurement environment for more than 2 hours, and then covered with the above-mentioned moisture permeable cup as a moisture permeable sheet to make it airtight. Then, a moisture permeable cup with 40g of water added was placed in a constant temperature and humidity chamber under the environment of temperature 20°C, relative humidity 30%, and wind speed 2.4m / s, and the total mass reduction of water and moisture permeable cup after 1 hour was converted into the test piece per 1m 2 The mass after 24 hours was calculated as the moisture permeability. In addition, the moisture permeability was also measured under the same conditions at a temperature of 20°C, a relative humidity of 65%, and in an environment with virtually no wind (wind speed of 0.1 m / s).

[0159] (2) Anti-blocking property (evaluation of roll state)

[0160] The humidifying laminate was heated at 70° C. for 15 hours in a rolled sheet, and then the sheet was pulled out by hand, and the blocking property was evaluated as follows.

[0161] Large: Unable to pull out the film.

[0162] Middle: After the sheet is pulled out, it is deformed.

[0163] Small: After pulling out the sheet, the sheet is not deformed at all.

[0164] (Evaluation of film status)

[0165] Two 25 mm x 100 mm long strips of the above humidifying laminate were prepared, and water was dripped onto the nonporous membrane side of one sample, and then the nonporous membrane of the other humidifying laminate was laminated so that water was spread all over the surface. The laminated samples were heated at 55°C for 1 hour, and the peel strength was measured using a Tensilon.

[0166] (3) Scale accumulation test

[0167] 7 ml of hardness-adjusting water (Ca hardness 1435 mg / L) was dripped onto the non-porous membrane side of the above-mentioned humidification laminate cut into a circle with a diameter of 7 cm, and dried at 60° C. for 4 hours. The non-porous membrane side of the obtained scale accumulation sample was washed by soaking in pure water for 15 minutes, and dried at 60° C. for 30 minutes. The surface of the dried non-porous membrane was observed by SEM to see if there was scale accumulation.

[0168] [Table 1]

[0169] (Table 1)

[0170]

[0171] [Table 2]

[0172] (Table 2)

[0173]

[0174]

[0175] As shown in the evaluation results of Example 1, the humidification laminate of the present disclosure has sufficient moisture permeability and can suppress the accumulation of scale components. In contrast, when a non-porous film is not formed as in Comparative Example 1, the accumulation of scale components is the result. The non-porous film having a cationic portion can suppress the accumulation of scale components, and thus it is shown that the moisture permeability can be maintained for a long time. In addition, as shown in Examples 1 to 5, since it is not easy to cause adhesion between the moisture permeable films, it is estimated that even a moisture permeable film type humidifier that can suppress the scattering of impurities will not cause a decrease in moisture permeability due to adhesion between the moisture permeable films, and sufficient moisture permeability can be maintained for a long time.

[0176] Modifications of the invention disclosed herein will be described below.

[0177] [Note 1]

[0178] A humidifying laminate comprising: a porous reinforcing material; and a nonporous membrane laminated on at least one surface of the porous reinforcing material and functioning as a nonporous membrane, wherein the nonporous membrane contains a thermoplastic resin having a cationic portion or an anionic portion.

[0179] [Note 2]

[0180] The humidifying laminate according to Supplementary Note 1, wherein the non-porous membrane is disposed on the water side of the liquid with respect to the porous reinforcing material, and absorbs water from the liquid and releases it into the air.

[0181] [Note 3]

[0182] The humidifying laminate according to Appendix 1 or 2, wherein the cation portion contains a group containing an ammonium ion or a group capable of forming an ammonium ion.

[0183] [Note 4]

[0184] The humidifying laminate according to any one of Appendixes 1 to 3, wherein the thermoplastic resin has a hydrophilic portion, and the hydrophilic portion contains a structural unit represented by the following formula (1).

[0185] [Chemical formula 1]

[0186]

[0187] (R1 and R2 independently represent a hydrogen atom or a methyl group.)

[0188] [Note 5]

[0189] The humidifying laminate according to any one of Appendixes 1 to 4, wherein the thermoplastic resin has a hydrophobic portion, and the hydrophobic portion contains a structural unit represented by the following formula (2) and / or the following formula (3).

[0190] [Chemical formula 2]

[0191]

[0192] (R1 represents a hydrogen atom or a methyl group, and R3 represents a hydrogen atom or an alkyl group having 1 to 2 carbon atoms.)

[0193] [Chemical formula 3]

[0194]

[0195] (R1 represents a hydrogen atom or a methyl group, and R4 represents a branched alkyl group having 3 or more carbon atoms.) [Supplementary Note 6]

[0196] The laminate according to any one of Appendixes 1 to 5, wherein the nonporous film contains an antiseptic.

[0197] [Note 7]

[0198] The humidifying laminate according to Supplementary Note 6, wherein the average particle diameter of the preservative is larger than the film thickness of the non-porous film.

[0199] [Note 8]

[0200] The humidifying laminate according to any one of Appendixes 1 to 7, wherein the nonporous film contains an anti-blocking agent.

[0201] [Note 9]

[0202] The humidifying laminate according to Supplementary Note 8, wherein the average particle diameter of the anti-blocking agent is larger than the film thickness of the non-porous film.

[0203] [Note 10]

[0204] The humidifying laminate according to any one of Appendixes 1 to 9, wherein the nonporous film contains a leveling agent.

[0205] [Note 11]

[0206] The humidifying laminate according to any one of Appendixes 1 to 10, wherein the nonporous film is applied so as to cover at least one surface of the porous reinforcing material.

[0207] [Note 12]

[0208] A humidifier provided with a plurality of bag-shaped water-retaining containers formed by bonding the humidifying laminate according to Supplementary Note 11 to a frame.

[0209] [Note 13]

[0210] An air conditioner equipped with the humidifier as described in Supplementary Note 12.

[0211] [Note 14]

[0212] A ventilation device equipped with the humidifier as described in Appendix 12.

[0213] [Note 15]

[0214] An air purifier equipped with the humidifier as described in Appendix 12.

[0215] Description of Reference Numerals

[0216] 1: laminate;

[0217] 11: Porous reinforcement material;

[0218] 11a: One surface of the porous reinforcement material;

[0219] 12: Non-porous membrane.

Claims

1. A humidifying laminate, comprising: a porous reinforcing material; and a non-porous film laminated on at least one surface of the porous reinforcing material and functioning as a moisture-permeable film, wherein: The nonporous film contains a thermoplastic resin having a cationic portion or an anionic portion.

2. The humidifying laminate according to claim 1, wherein The non-porous membrane is disposed on the water side of the liquid relative to the porous reinforcing material, and is used to absorb water from the liquid and release it into the air.

3. The humidifying laminate according to claim 1 or 2, wherein The cationic portion contains a group including an ammonium ion or a group capable of forming an ammonium ion.

4. The humidifying laminate according to claim 1 or 2, wherein The thermoplastic resin has a hydrophilic portion, and the hydrophilic portion contains a structural unit represented by the following formula (1): In the formula, R1 and R2 independently represent a hydrogen atom or a methyl group.

5. The humidifying laminate according to claim 1 or 2, wherein The thermoplastic resin has a hydrophobic portion, and the hydrophobic portion contains a structural unit represented by the following formula (2) and / or the following formula (3), In formula (2), R1 represents a hydrogen atom or a methyl group, and R3 represents a hydrogen atom or an alkyl group having 1 to 2 carbon atoms. In formula (3), R1 represents a hydrogen atom or a methyl group, and R4 represents a branched alkyl group having 3 or more carbon atoms.

6. The humidifying laminate according to claim 1 or 2, wherein The non-porous film includes a preservative.

7. The humidifying laminate according to claim 6, wherein The average particle size of the antiseptic is larger than the film thickness of the non-porous film.

8. The humidifying laminate according to claim 1 or 2, wherein The nonporous film includes an antiblocking agent.

9. The humidifying laminate according to claim 8, wherein The average particle size of the anti-blocking agent is greater than the film thickness of the non-porous film.

10. The humidifying laminate according to claim 1 or 2, wherein The nonporous film includes a leveling agent.

11. The humidifying laminate according to claim 1 or 2, wherein The non-porous film is applied in a manner covering at least one surface of the porous reinforcing material. 12 . A humidifier comprising a plurality of bag-shaped water-retaining containers formed by bonding the humidifying laminate according to claim 11 to a frame.

13. An air conditioner equipped with the humidifier according to claim 12.

14. A ventilation device equipped with the humidifier according to claim 12.

15. An air purifier equipped with the humidifier according to claim 12.

Citation Information

Patent Citations

  • Vaporization filter for humidification, vaporization filter laminated body for humidification and humidification method using them

    JP2011002126A

  • Delivery system

    JP2022096877A

  • Antifog laminate

    CN109641432A

  • Humidifier of gas for breathing

    JP1996266631A

  • Laminate body

    WO2021200382A1